O lugar do trabalho e do trabalhador na imprensa diária amazonense (1906-1918) - Ferreira, Jéssica Maria de Souza (Brasil, 2024)
This work was designed to try to understand through the use of newspapers from the last century, Correio do Norte and A Capital, which circulated in the city of Manaus, and thus better understand in two distinct periods how each one interpreted, represented, or judged the situations involving the living conditions and especially the working conditions of workers in this constantly changing city.